Use of Selected Natural Calcium Sources for Calcium Enrichment of Crisp Rice - Chaimongkol, Laksana (KKU Science Journal, 2012)
Fish bone powder, small fresh water shrimp powder and anchovy powder were produced and used as calcium sources for calcium enriched crisp rice production. The addition levels suitable for human taste as well as the effects of natural calcium sources on the quality of crisp rice were experimentally determined in this study. The formula with 17.5% by weight of the three calcium sources had the closest acceptance score to that of local fish crisp rice. According to the consumer test done with 100 school children and 100 adults, small fresh water shrimp powder enriched crisp rice was the best accepted. The linear expansion decreased as the amounts of calcium sources increased but there was no change for crispiness. A 17.5% addition level and per one serving (30 g) of crisp rice, the fish bone enriched crisp rice provided 46% RDI; small fresh water shrimp enriched gave 22% RDI; and anchovy enriched contributed 29% RDI of calcium. The study has demonstrated that fish bone powder, small fresh water shrimp powder and anchovy powder are good sources for production of calcium enriched crisp rice. The largest effect on calcium intake is achieved, among these options, with fishbone powder, which is also cost effective. In contrast shrimp powder is the least likely option due to its high cost.